Book Review Book review of: Meaningful Assessment in Interdisciplinary Education: A Practical Handbook for University Teachers - Albert Pilot (Journal of the European Honors Council, 2023)
The authors stress that assessment is important as an integral building block of all learning, when assessment stimulates learning and is based on intrinsic motivation. This book focusses on twenty examples in higher education of teachers who in an innovative way assess competences of their students, like integration of disciplines, cooperation, reflection and critical thinking. Many examples are from honors programs in European higher education.